RESISTING AND PRODUCING: EXPERIENCES OF PARTICIPATION AND COOPERATION IN AGRARIAN REFORM IN SOUTHERN BRAZIL - Antonio Pasquetti , Luis; Pereira de Andrade, Manoel; Sérgio Dias Claudino, Lívio (Revista Gênero e Interdisciplinaridade, 2026)
This work is an offshoot of a nationwide research project on "Cooperativism and Associativism in Agrarian Reform Areas: Potentialities and Challenges." The data presented in this article refer to 28 cooperatives and one Central Cooperative, one Credit Cooperative, and two Associations, totaling 31 cooperative organizations in the Southern Region of Brazil, built by peasant agriculture. We observed the broad and significant participation of women and young people, among other important results.